Theoretical Perspectives on Learning Motivation and Its Influence on Arabic Language Achievement A Literature Study - M. Ali Karmani (Journal of Islamic Religious Studies, 2026)
This study examined the theoretical perspectives on learning motivation and their influence on Arabic language achievement through a literature study approach. Learning motivation has become one of the most influential psychological factors affecting students’ engagement, persistence, and academic success in Arabic language education. However, previous studies have generally focused on isolated motivational variables without comprehensively integrating major motivational theories within Arabic language learning contexts. Therefore, this study aimed to analyze the major theoretical perspectives on learning motivation, examine the influence of motivation on Arabic language achievement, and identify the motivational factors contributing most significantly to successful Arabic language learning. This research employed a qualitative literature study design. Data were collected from scholarly books, peer-reviewed journal articles, conference proceedings, and academic publications published within the last ten years. The collected data were analyzed using descriptive qualitative analysis through data reduction, categorization, interpretation, and conclusion drawing. The findings revealed that intrinsic motivation, extrinsic motivation, self-determination theory, self-efficacy theory, and socio-educational perspectives constitute the major theoretical foundations of motivation in Arabic language education. The study further demonstrated that learning motivation significantly influences students’ academic engagement, communicative participation, language skills development, learning strategies, psychological confidence, and overall Arabic language achievement. In addition, internal, external, instructional, environmental, and sociocultural motivational factors were identified as important contributors to sustainable Arabic language learning success. The study concluded that motivation is a multidimensional determinant of successful Arabic language education and should become a central consideration in instructional practices and curriculum development.